2018
DOI: 10.1523/jneurosci.2891-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Tactile Input Patterns Decoded at Comparable Levels But Different Time Scales in Neocortical Neurons

Abstract: The presence of contralateral tactile input can profoundly affect ipsilateral tactile perception, and unilateral stroke in somatosensory areas can result in bilateral tactile deficits, suggesting that bilateral tactile integration is an important part of brain function. Although previous studies have shown that bilateral tactile inputs exist and that there are neural interactions between inputs from the two sides, no previous study explored to what extent the local neuronal circuitry processing contains detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
3
14
0
Order By: Relevance
“…We use a recently introduced approach that is based on low-intensity electrical activation of tactile afferents in predefined complex spatiotemporal patterns, with the primary purpose of obtaining maximal reproducibility for a varied set of non-trivial tactile input patterns. This approach overcomes limitations associated with mechanical skin stimulation (see Discussion) and provides a highly sensitive tool to analyze the precision by which the spike output of a neuron contains information about the type of tactile input received (Genna et al, 2018;Oddo et al, 2017). We find that individual neurons can decode tactile input patterns to a non-adjacent, non-dominant digit at a comparable or even a higher level than for inputs to the dominant digit while also decoding which digit the input originated from.…”
Section: Introductionmentioning
confidence: 85%
“…We use a recently introduced approach that is based on low-intensity electrical activation of tactile afferents in predefined complex spatiotemporal patterns, with the primary purpose of obtaining maximal reproducibility for a varied set of non-trivial tactile input patterns. This approach overcomes limitations associated with mechanical skin stimulation (see Discussion) and provides a highly sensitive tool to analyze the precision by which the spike output of a neuron contains information about the type of tactile input received (Genna et al, 2018;Oddo et al, 2017). We find that individual neurons can decode tactile input patterns to a non-adjacent, non-dominant digit at a comparable or even a higher level than for inputs to the dominant digit while also decoding which digit the input originated from.…”
Section: Introductionmentioning
confidence: 85%
“…In order to achieve as realistic spatiotemporal patterns of tactile sensor activation as possible, while preserving the aim of high reproducibility of the patterns, we used an artificial fingertip equipped with four neuromorphic sensors to generate a set of spatiotemporal patterns of skin activation to be used in the electrical interface with the rat skin. The procedures have previously been described in greater detail and the patterns used here were the same as before (Oddo et al , 2017; Genna et al , 2018; Enander et al , 2019). As discussed in this previous work, the artificial fingertip allowed synthesising spatiotemporal patterns of skin sensor activation at quasi-natural firing rates that follow a natural overall temporal modulation, or ‘envelope’, that the biological skin sensors are known to display under dynamic indentation (Jenmalm et al , 2003).…”
Section: Methodsmentioning
confidence: 99%
“…We previously introduced a method to deliver such reproducible and diversified spatiotemporal input patterns by electrical activation of tactile afferents in local digit skin and showed that cells in the primary somatosensory cortex (S1) of the rat are capable of decoding these tactile inputs with high accuracy (Oddo et al, 2017). Using this approach, we recently reported that the neurons of the S1 cortex have access to information about the “what” component of ipsilateral tactile inputs, just like they have for contralateral inputs (Genna et al, 2018). Here, we show that in non-paw S1 regions and in non-S1 regions across the dorsal neocortical surface, including within visual cortical areas, the responses of individual neocortical neurons contain information about the “what” component of tactile inputs to the second digit of the forepaw.…”
Section: Introductionmentioning
confidence: 99%